Effect of job satisfaction, employee engagement, and work culture on employee performance during the Covid-19 pandemic - Gunawan, Akbar; Wahyuni, Nuraida; Baridzualdi, Baridzualdi; Katili, Putiri Bhuana; Setiawan, Hadi; Yulianti, Nani (Universitas Sultan Ageng Tirtayasa, 2022)
XYZ is a manufacturing company producing paper and cardboard boxes for packaging. Based on field observations, the Covid-19 pandemic also impacts XYZ employees, namely changes in work habits. These changes make employees experience difficulties at work and make it difficult for them to meet production targets. Based on this, there are indications of a decrease in employee performance. Therefore, the researchers took several approaches to things that affect employee performance. This study aims to determine the effect of job satisfaction on employee performance, attachment to employee performance, and work culture on employee performance. The results obtained from these objectives are that the job satisfaction variable has a positive and significant effect on the employee performance variable, the employee engagement variable has a positive and significant effect on employee performance, and the work culture variable has a positive and significant influence on the employee performance variable.